Subcutaneous immunoglobulin as first‐line therapy in treatment‐naive patients with chronic inflammatory demyelinating polyneuropathy: randomized controlled trial study. (21st December 2016) - Markvardsen, L. H.; Sindrup, S. H.; Christiansen, I.; Olsen, N. K.; Jakobsen, J.; Andersen, H.; ,
Abstract : Background and purpose: Subcutaneous immunoglobulin (SCIG) is effective as maintenance treatment in chronic inflammatory demyelinating polyneuropathy (CIDP). We investigated whether multiple subcutaneous infusions are as effective as conventional therapy with intravenous loading doses in treatment‐naive patients with CIDP. Methods: Twenty patients fulfilling the clinical and electrophysiological criteria for CIDP were included and treated with either SCIG (0.4 g/kg/week) for 5 weeks or intravenous immunoglobulin (IVIG) (0.4 g/kg/day) for 5 days. After 10 weeks, patients were switched to the opposite treatment arm and followed for a further 10 weeks. All participants were evaluated at weeks 0, 2, 5 and 10 during both therapies. Primary outcome was combined isokinetic muscle strength (cIKS). Secondary outcomes were disability, clinical evaluation of muscle strength and the performance of various function tests. Results: All participants received both therapies, 14 completing the protocol. Overall, cIKS increased by 7.4 ± 14.5% ( P = 0.0003) during SCIG and by 6.9 ± 16.8% ( P = 0.002) during IVIG, the effect being similar ( P = 0.80). Improvement of cIKS peaked 2 weeks after IVIG and 5 weeks after SCIG. Disability improved during SCIG treatment only. Muscle strength determined by manual muscle testing improved after 5 and 10 weeks during SCIG but only after 5 weeks during IVIG. The remaining parameters improved equally during both treatments. Plasma immunoglobulin G levels at baseline and improvement of cIKS were related. Conclusion: In treatment‐naive patients with CIDP, short‐lasting SCIG and IVIG therapy improve motor performance to a similar degree, but with earlier maximal improvement following IVIG than SCIG treatment.